Removal of trivalent chromium using hexane‐extracted spent bleaching earth - Low, K.S.; Lee, C.K. (Marcel Dekker, 1996)
The removal of trivalent chromium from synthetic solution by hexane-extracted spent bleaching earth was investigated on a laboratory scale under various conditions. Data obtained followed the Langmuir isotherm for the Cr(III)-hexane extracted spent bleaching earth. Maximum sorption was calculated to be 9.48 mg/g at room temperature. Copyright © 1996 by Marcel Dekker, Inc.